Protection conferred by immunization plans using live and inactivated Salmonella vaccines against the challenge with S. Enteritidis - Joaquim, Patricia Estefania; Balbiani, Facundo; Sara, Lucas; Sesti, Luiz; Socas, Maria Laura; Quispe Chosgo, Tamara Belen; Arenas Mosquera, David José; Sarabia, Jaime; Paulet, Pascal; Chacana, Pablo (INNOZH, 2026)
Poster